Chondrichthyans from the Grippia bonebed (Early Triassic) of Marmierfjellet, Spitsbergen. - Bratvold, Janne (2016)
The Permian Triassic Mass Extinction (PTME) is the most crucial extinction in earth’s history. The recovery of terrestrial and marine habitats and ecosystems are scarcely explored due to the minute material excavated from the Early Triassic. This study describes the taxa and ecology of the chondrichthyan assemblage from an Early Triassic Grippia Niveau bonebed. The Grippia bonebed is located at Marmierfjellet in Flowerdalen, Isfjorden area of Spitsbergen. The bonebed is found in the Vendomdalen Member, Vikinghøgda Formation, Early Triassic (Spathian). This Early Triassic bonebed is unique in Spitsbergen due to its richness of chondrichthyans and ichthyopterygians. Over 550 phosphatized chondrichthyan teeth, three fin spines and one cephalic spine identified to 7 genera and 15 species of chondrichthyans are described herein. Of the 15 identified species, 8 of them are new to the Grippia Niveau. The Hybodontiformes represent 5 of the identified genera, where most of the identified species belong to the Hybodus and Acrodus. The heterodont dentition is frequently overlooked in the identification of chondrichthyan teeth to species or genera. This results in several morphospecies, species that should be viewed as synonyms. In this paper the problem is discussed for the close resemblance of Hybodus sasseniensis and H. rapax, of Acrodus scaber and A. spitzbergensis and the Acrodus genus in general. Hybodus sasseniensis was previously only known from the older Dienarian substage, this study concludes that the species is also found in the younger Spathian substage. H. sasseniensis has up to 7 lateral cusplets beside the central cusp, and the new material consists of the largest identified tooth for this species from Spitsbergen. The presence of Hybodus microdus in the material is uncertain, due to the more than 7 times larger mesio-distal length of the teeth than previously described by Stensiö (1921), but raise the question of the “Lilliput” effect after the PTME. A species new to Spitsbergen, Acrodus gaillardoti, is described. The A. gaillardoti is previously known from the younger Anisian – Ladinian stage in the upper Muschelchalk bonebed in Bissendorf. The Neoselachii (modern shark) was only known from Spitsbergen by a Nemacanthus fin spine, whereas this study gives the first teeth descriptions of two neoselachian species. The shallow epicontinental Boreal Sea of the Spathian consisted of a majority of active chondrichthyan hunters with cutting and tearing dentition and durophagous chondrichthyans with grinding dentition.